Identification Model Of Job Description, Compensation, Rotation Work And The Impact On Employee Performance - Anwar, Yohni; Dewanto, Vishnu (International Journal of Science, Technology & Management, 2022)
The research objective is to improve the competence and performance of employees at Indosat Ooredo outlets based on the SEM model on the variables of training and development, job description , compensation and job rotation. The method of analysis in this study uses a Structural approach Equation Modeling (SEM). The SEM model is used to predict the training and development model, job description , compensation and job rotation on work culture and employee performance. The population in this study were 120 employees at Indosat Ooredoo outlets . The sample of this research data was taken based on the census sample, that is, all of the population was used as a sample, namely 120 respondents. The data used is primary data where respondents get data for the questionnaire. Meanwhile, the data collection method used in this study was a questionnaire and interviews. The results showed that direct competence had no effect on job satisfaction while job description, compensation and job rotation had a significant effect on job satisfaction. Directly competence, job description and job rotation and job satisfaction have a significant effect on employee performance while compensation is not significant on employee performance. Indirectly, satisfaction has a significant role in mediating competence, job description and compensation on employee performance, while job satisfaction has no role in mediating job rotation on employee performance.